THE JOURNEY OF JOURNAL ON MATHEMATICS EDUCATION: FROM LOCAL TO GLOBAL - Zulkardi Zulkardi; Rully Charitas Indra Prahmana (Journal on Mathematics Education, 2021)
One of indicators to determine the quality of a journal can be observed from how many indexing institutions recognized it nationally and globally, such as Sinta, Scopus, and ScimagoJR. Furthermore, the rank of a journal in the indexing institution will add more value to the reputation of a journal. However, few journal editors are willing to share their experiences in managing a journal, from the beginning to getting recognition at the international level. Thus, this article describes the journey of the first journal in the mathematics education field from Indonesia called the Journal on Mathematics Education (JME), which is globally recognized and indexed on Scopus. JME's journey to gain global recognition is narrated in a structured way, starting from the history of journal formation, recognition at the local level, strategies to get authors from various countries, promotional activities to get credit, until finally getting a global position. In addition, this article also describes many contributions from world-class Mathematics Education researchers who have published their research results in JME. Finally, this article also describes the position of JME at national and international levels based on the data of several indexing institutes and JME's future targets.